Identifying unmet antithrombotic therapeutic need, and implications for stroke and systemic embolism in atrial fibrillation patients: a population-scale longitudinal study - Fatemeh Torabi (European Heart Journal Open, 2022)
AimsGuidelines recommend anticoagulation (AC) in atrial fibrillation (AF) to reduce stroke and systemic embolism (SSE) risk; however, implementation has been slow across many populations. This study aimed to quantify the potential impact of changing prevalence of AF, associated risk, and AC prescribing on SSE hospitalizations and death.Methods and resultsWe evaluated temporal trends of AF, CHA2DS2-VASc, antithrombotic prescriptions, SSE hospitalizations, death, and their associations between 2012 and 2018 in a longitudinal cohort of AF patients in Wales UK. Multi-state Markov models were used to estimate expected SSE rates given the AC coverage, adjusting for CHA2DS2-VASc scores. SSE rates were modelled for various past and future AC scenarios. A total of 107 137 AF patients were evaluated (mean age = 74 years, 45% female). AF prevalence increased from 1.75 to 2.22% (P-value <0.001). SSE hospitalizations decreased by 18% (2.34–1.92%, P-value <0.001). Increased AC coverage from 50 to 70% was associated with a 37% lower SSE rate, after adjustment for individual time-dependent CHA2DS2VASc scores. The observed AC increase accounted for approximately 80 fewer SSE hospitalizations per 100 000/year. If 90% AC coverage had been achieved since 2012, an estimated 279 SSE per 100 000/year may have been prevented. Our model also predicts that improving AC coverage to 90% over the next 9 years could reduce annual SSE rates by 9%.ConclusionWe quantified the relationship between observed AC coverage, estimating the potential impact of variation in the timing of large-scale implementation. These data emphasize the importance of timely implementation and the considerable opportunity to improve clinical outcomes in the Wales-AF population.